2005
DOI: 10.1159/000086490
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Effector Molecules and Complicated Malaria

Abstract: In this review I attempt to advance hypotheses that might help contribute toward understanding the molecular pathogenesis of cerebral malaria (CM) and other complications based on a now widely accepted argument that the illness and pathology occasioned by Plasmodiumfalciparum infection might not necessarily be due to the direct effects of the parasite’s ‘toxins’ and/or exoantigens or even its sequestration and consequent attendant effects in vital organs but rather to the parasite’s mediated production of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 233 publications
0
5
0
Order By: Relevance
“…An interesting finding was the presence of leukocyte and erythrocyte derived-MPs during acute P. vivax malaria. The role of leukocytes in malaria pathogenesis is still not fully understood; nevertheless, it has been shown that these cells are the main source of pro-inflammatory cytokines, especially TNFα which is highly pyrogenic [ 32 ]. The presence of MPs derived from these cells provides evidence for their activation in acute vivax malaria.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding was the presence of leukocyte and erythrocyte derived-MPs during acute P. vivax malaria. The role of leukocytes in malaria pathogenesis is still not fully understood; nevertheless, it has been shown that these cells are the main source of pro-inflammatory cytokines, especially TNFα which is highly pyrogenic [ 32 ]. The presence of MPs derived from these cells provides evidence for their activation in acute vivax malaria.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a key immunoregulator that counteracts excessive inflammatory responses caused by Th1 cells (Nyangoto, 2005) and pro-inflammatory cytokines such as TNF-α and IFN-γ, thus confers protective immunity to erythrocytic malaria parasites (Artavanis-tsakonas et al, 2003). In experimental cerebral malaria, the inhibitory effect of IL-10 on the release of TNF-α and IFN-γ has been found to benefit the host by counteracting the pathological role of macrophage (Kossodo et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to P. vivax, where a direct and protective interaction between infected erythrocytes and CD8 + T cells has been demonstrated. This effect is attributed to the MHC-I expression of reticulocytes as host cells of P. vivax, which makes them susceptible for a granulysinmediated permeabilization and subsequent GrzB-mediated killing (15).…”
Section: Discussionmentioning
confidence: 99%
“…In P. falciparum malaria, numerous attempts were undertaken to correlate the T cell phenotype and or cytokine production with the clinical outcome of the disease. Several studies indicate that the ratio of pro-inflammatory TNFα and anti-inflammatory IL-10 may influence disease outcome (15). Although this might represent a reasonable explanation for disease manifestation this dichotomy is not present in every cohort studied.…”
Section: Introductionmentioning
confidence: 95%